Culture of copepod Oithona simplex (Farran, 1913) and its potential as live food for flower crab, Portunus pelagicus (Linnaeus, 1758) larvae - Mat Noor, Nur Syuhada (2017)
Research on Oithona simplex was carried out to further assess its potential as live food candidate for hatchery crab larval rearing. Although several species copepods from genus Oithona was proven to be good for fish larval rearing, no trial had ever been carried out using O. simplex during crab larval rearing and its life cycle development of this O. simplex has not been studied. All experiments were done at the International Institute of Aquaculture and Aquatic Sciences, Port Dickson and specimens were obtained from nearby coastal waters. The larval development of O. simplex was studied under laboratory condition of 30 ⁰C and with 12 hours light and 12 hours dark photoperiod. The developmental stages were divided into 6 naupliar stages (NI, NII, NIII, NIV, NV, NVI), 5 copepodite stages (CI, CII, CIII, CIV, CV) and an adult (CVI) stage. The different larval stages of this species were described. The life cycle period lasted for 5 to 6 days. Effect of some environmental parameters on the reproduction and development of O. simplex were also studied. This is to gather the optimum environmental condition for the culture of the species. Four different salinity levels viz. 20, 25, 30 and 35 ppt, three different temperatures of 25, 30 and 35 ºC, three different photoperiods representing 12h light (L): 12h dark (D), 1h (L):23h (D), 24h (L):0h (D) and three light intensities of 5, 20, 35 μmol m-2 s-1 were employed in this study. Oithona simplex can tolerate a wide range of salinity of 20-35 ppt. The optimum temperature required for the maximum reproduction of O. simplex was 30 ºC. The overall reproductive process was highest under the lowest light intensity (5 μmol m-2 s-1) compared to other light intensities. In addition, the overall reproduction and fastest development time were achieved by copepod reared under photoperiod 12h light (L): 12h dark (D) condition. The result of this study showed that O. simplex had a high population growth, short generation time, high reproductive potential, and a wide range of tolerance to environmental conditions. Survival and specific growth rates of flower crab larvae from zoea 1 to megalopa stage were studied by feeding them with three different live food options that comprised of O. simplex alone, Artemia nauplii in combination with O. simplex and only Artemia nauplii. The highest survival was achieved by crab larvae fed with the combination of O. simplex and Artemia nauplii (3.16%), followed by those fed with O. simplex (1.31%) and Artemia nauplii (0.95%). Meanwhile, the highest specific growth rates were achieved by larvae fed with the combination of both live foods (28.4 %) followed by Artemia nauplii only (27.2%) and only O. simplex (25.6%). No significant difference was found on the final length of crab larvae in those three different treatments. The result from this study showed that O. simplex meets the several requirements needed as live feed for crab larvae which indicated that it can be used to replace partially imported Artemia cyst during crab larval rearing.